2003
DOI: 10.1046/j.1523-1755.2003.00716.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of somatostatin receptors 3, 4, and 5 in mouse kidney proximal tubules

Abstract: Expression of SSTR3, SSTR4, and SSTR5 in mouse proximal tubules complements the expression of SSTR1 and SSTR2 in collecting ducts as seen in other species. Taken together, the kidney is one of few organs expressing all five somatostatin receptors outside of the nervous system and pancreas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…The high kidney uptake of 177 Lu-octreotate in the present study can be explained by the fact that kidneys in mice are one of few non-NE organs besides the pancreas that express all five SSTR (45)(46)(47). Further, there is a difference in the expression pattern of SSTR between human and mice kidneys, which complicates the translation of uptake data and dosimetry between species.…”
Section: Discussionmentioning
confidence: 72%
“…The high kidney uptake of 177 Lu-octreotate in the present study can be explained by the fact that kidneys in mice are one of few non-NE organs besides the pancreas that express all five SSTR (45)(46)(47). Further, there is a difference in the expression pattern of SSTR between human and mice kidneys, which complicates the translation of uptake data and dosimetry between species.…”
Section: Discussionmentioning
confidence: 72%
“…Particular peptides may also be taken up by ligand-specific receptors, such as somatostatin receptors (15). Abundant expression of all somatostatin receptor subtypes has been described in the human and murine kidney (16,17), and subtypes 3 and 4 were found in the rat kidney (18). Rolleman et al retrospectively studied 111 In-octreotide scans of patients who were scanned before and during treatment with unlabeled octreotide.…”
Section: Proximal Tubular Reabsorption and Processingmentioning
confidence: 99%
“…The study showed expression of all five ssts in the brain and pituitary, whereas other investigated organs, e.g., lungs, liver, and pancreas, varied in their tissue sst expression. The mRNAs for all five ssts were also detected in mouse brain (Fehlmann et al 2000) and in the retina (Cristiani et al 2002), whereas only sst [3][4][5] were expressed in the kidney (Bates et al 2003). However, to elucidate the more exact cellular distribution of sst, immunohistochemical (IHC) investigations are needed.…”
mentioning
confidence: 99%